2010
DOI: 10.1159/000297749
|View full text |Cite
|
Sign up to set email alerts
|

Time of Birth, Residential Solar Radiation and Age at Onset of Multiple Sclerosis

Abstract: Backgrounds/Aim: Gestational and early life events have been suggested to contribute to multiple sclerosis (MS) susceptibility. We assessed the effects of time and place of birth on the age at onset of MS symptoms. Methods: We selected a national cohort of 967 veterans from the Multiple Sclerosis Surveillance Registry for whom month and season (time) of birth, and birthplace (city and state) were available. Multiple linear regression analyses were used to examine the association between time of birth, birthpla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
29
0
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(32 citation statements)
references
References 61 publications
(52 reference statements)
2
29
0
1
Order By: Relevance
“…Riise and Klauber [5] found that among contemporaneous MS patients, a higher degree of residence clustering during adolescence was associated with younger age at disease onset. Moreover, in our earlier study we found associations between season and place of birth and age at MS symptom onset [29] . A recent study found that the effect of the vitamin D receptor gene in determining MS F igures in parentheses indicate percentages.…”
Section: Discussionmentioning
confidence: 66%
“…Riise and Klauber [5] found that among contemporaneous MS patients, a higher degree of residence clustering during adolescence was associated with younger age at disease onset. Moreover, in our earlier study we found associations between season and place of birth and age at MS symptom onset [29] . A recent study found that the effect of the vitamin D receptor gene in determining MS F igures in parentheses indicate percentages.…”
Section: Discussionmentioning
confidence: 66%
“…Accordingly, even if the simple encounter with EBV remains in the great majority of cases a banal infection without apparent deleterious long-term consequences, it could also, in some cases, be the first event triggering a long-lasting deleterious immunological cascade, worsened both by a late primo infection occurrence with symptomatic infectious mononucleosis and by the persistence of a high anti-EBNA1 level, [Gale and Martyn, 1995;Alonso and Hernan, 2008;Simpson et al 2011;Sloka et al 2011a], at a continental level [Kurtzke, 1995;Puggliatti et al, 2006], in large countries, such as the United States [Acheson et al 1960;Kurtzke et al 1985, Kurtzke, 2008, the former Soviet Union [Boiko et al 1995] and Australia [van der Mei et al 2001;Taylor et al 2010] and even in comparatively smaller countries, such as New Zealand [Taylor et al 2008] and France, at least in farmers [Vukusic et al 2007]. MS prevalence may change after migrations occurred during the second decade of life, with, for example, a beneficial effect for people who have migrated from a high-latitude region (with a high MS prevalence) to a sunnier, lower-latitude region (with a low MS prevalence) [Kurtzke et al 1985;Gale and Martyn, 1995;Hammond et al 2000;Munger, 2007a, 2007b;Handel et al 2010a;McDowell et al 2010;McLeod et al 2011]. It should be noted that a reverse migration, that is, from a lowlatitude region to a higher-latitude region, has less effect on MS prevalence, as though the environmental protection acquired in infancy and childhood, maybe related to the sunny climate of these regions (see below), is long lasting at adult age for these migrants.…”
Section: Genetic Risk Factors For Multiple Sclerosis Possibly Involvimentioning
confidence: 99%
“…The geographical difference of MS incidence can be partly explained by exposure to sunshine [76] . The UV-induced production of vitamin D in human body is an independent environmental factor that varies geographically in a pattern roughly the same as that of MS prevalence.…”
Section: Vitamin D and Msmentioning
confidence: 99%